Streptococcus pneumoniae Upper Respiratory Carriage in Costa Rican Children with Otitis Media before the Introduction of the Heptavalent Conjugated Vaccine in the National Immunization Program - Ulloa, Catalina (2013)
Objective: The aim of this study was to analyze the NP/OP S. pneumoniae serotype distribution and potential vaccine coverage in Costa Rican children with Otitis Media (OM) before the introduction of PCV-7 in the National Immunization Program (NIP). Methods: Between 2002 and 2006, NP and OP samples were obtained from 641 children from 6 to 79 months of age, at the time of OM diagnosis. S. pneumoniae serotyping and antimicrobial susceptibility were performed. Results: 386 S. pneumoniae isolates were recovered. The most common S. pneumoniae serotypes (ST) were: ST 6B, ST 14, ST 19F. Penicillin non-susceptibility was observed among 57% of the isolates obtained from children < 24 months of age. 15% strains were multidrug resistant. Potential vaccine coverage was: PCV-7: 60%; PCV-10: 62%; and PCV-13: 76% and against penicillin non-susceptible and multidrug resistant isolates was: PCV-7; 59% and 83%, respectively; PCV-10: 60% and 85%, respectively and PCV-13: 74% and 96%, respectively. Conclusions: S. pneumoniae was isolated from the NP and/or OP in the majority (59%) of studied children with OM. At a statistical significant level, only serotype 3 was more frequently isolated among children >24 months of age. Antibiotic non-susceptibility and MDR were significantly higher in children <24 months of age. This study demonstrates that PCV-13 offers the highest potential vaccine coverage and serves to assess the impact of introduction of one of the conjugated vaccines in the NIP in Costa Rica.